2011
DOI: 10.1158/0008-5472.can-11-1291
|View full text |Cite
|
Sign up to set email alerts
|

p38γ Promotes Breast Cancer Cell Motility and Metastasis through Regulation of RhoC GTPase, Cytoskeletal Architecture, and a Novel Leading Edge Behavior

Abstract: Understanding the molecular alterations that confer cancer cells with motile, metastatic properties is needed to improve patient survival. Here we report that p38γ MAPK regulates breast cancer cell motility and metastasis, in part by controlling expression of the metastasis-associated small GTPase RhoC. This p38γ-RhoC regulatory connection was mediated by a novel mechanism of modulating RhoC ubiquitination. This relationship persisted across multiple cell lines and in clinical breast cancer specimens. Using a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 46 publications
3
76
0
Order By: Relevance
“…In this cohort of 81 breast cancer specimens, 70.5% of tumors had increased p38␥ expression, 21.3% had no change, and 8.2% had decreased p38␥ expression relative to the matched controls. These results are consistent with previous reports from us and others (23,31,32). Importantly, levels of p38␥ were increased significantly in ER-negative (ER Ϫ ) and in PR-negative (PR Ϫ ) specimens compared with their receptor-positive counterparts ( Fig.…”
Section: P38␥ Phosphorylates Er At Ser-118 In Vitro and In Vivo Andsupporting
confidence: 93%
See 1 more Smart Citation
“…In this cohort of 81 breast cancer specimens, 70.5% of tumors had increased p38␥ expression, 21.3% had no change, and 8.2% had decreased p38␥ expression relative to the matched controls. These results are consistent with previous reports from us and others (23,31,32). Importantly, levels of p38␥ were increased significantly in ER-negative (ER Ϫ ) and in PR-negative (PR Ϫ ) specimens compared with their receptor-positive counterparts ( Fig.…”
Section: P38␥ Phosphorylates Er At Ser-118 In Vitro and In Vivo Andsupporting
confidence: 93%
“…In addition, recent studies from others (28) and us (29) have shown that p38␥ can be selectively activated by certain stress stimuli, indicating its specific role in stress response. Because all MAPKs can phosphorylate the S/TP motif (30) such as Ser-118 in ER (10), p38␥ can stimulate breast cancer invasion and/or metastasis through binding and antagonizing ER (23), and/or additional pathways (31,32), p38␥ may therefore be a key MAPK to phosphorylate ER/Ser-118 in breast cancer (22). Moreover, p38␥ can increase c-Jun transcriptional activity through increasing c-Jun levels and by enhancing AP-1-dependent transcription (33).…”
Section: Estrogen Receptor ␣ (Er)mentioning
confidence: 99%
“…Dual inhibition of c-Src and p38 kinases p38MAPK kinase activity is reported to have an important role in the metastasis of TNBC tumors (37). Thus, we hypothesized that UM-164's ability to potently inhibit the p38 kinases is beneficial with regard to the observed anti-TNBC activities.…”
Section: Kinome-wide Profiling Of Um-164mentioning
confidence: 98%
“…Alternatively, activation of TGF-β receptor induces the transition of otherwise poorly migratory epithelial cancer cells into migratory mesenchymal cells (7). Downstream effectors, such as the Rho-GTPase family member RhoC, further stimulate invasiveness and cancer cell dissemination (8). Similarly, integrin adhesome molecules such as integrin α 5 β 1 , focal adhesion kinase (FAK), Src, and p130Cas were shown to be associated with metastatic activity (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%